THEMATIC INTERPRETATION AS AN INTEGRATIVE ‎EPISTEMOLOGICAL MODEL FOR CONTEMPORARY ‎ISLAMIC RELIGIOUS EDUCATION ‎ - Fadly, Ahmad; Samad, Duski; Mamad, Firdaus (International Journal of Multidisciplinary Reseach, 2025)
This study explores the thematic interpretation method (tafsir maudhu’i) as a significant approach to engaging the Qur’an with contemporary knowledge. The research is driven by the urgency to bridge Qur’anic guidance with the rapid advancement of modern sciences, which often lack ethical and spiritual grounding. The objectives are to outline the fundamental principles of tafsir maudhu’i, evaluate its contribution to the development of contemporary disciplines, and assess its broader implications for Islamic epistemology. Utilizing a library-based method, the study reviews both classical sources and recent scholarship. The findings indicate that tafsir maudhu’i demonstrates an integrative and context-sensitive character, offering applicable ethical foundations that can guide the interaction between revelation and social realities. Furthermore, this method provides a conceptual framework for constructing a paradigm of knowledge that unites scriptural insights with the demands of modern society. The research concludes that tafsir maudhu’i functions not only as a hermeneutical tool but also as an epistemological model capable of renewing Islamic thought in addressing global challenges.